A pseudotumoral lesion diagnosed for a hypertrofic fibrosis at the proximal stump in anterior tibialis tendon missed rupture: a case report - Samaila, Elena M.; Luiso, Filippo; Trivellin, Giacomo; Brunelli, Matteo; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2017)
The Anterior Tibialis is the most important muscle in ankle dorsiflexion. The anterior tibialis tendon (ATT)’s rupture is an infrequent condition which can be both traumatic and spontaneous. Clinic is poor and it is necessary to confirm the suspect by US or MRI. The reported case refers to a 40 years old man who had a direct trauma at ankle and midfoot which was originally conservatively treated for an ankle sprain. Three months later he returned with pain, swelling and paresthesia. MRI was performed showing a neoformation in the contest of ATT’s rupture. The patient underwent open excisional biopsy which was diagnostic for hypertrofic fibrosis. After two weeks, the symptoms were completely decreased and patient didn’t want to undergo surgery for tendon reconstruction because he had no limitation in daily activity life.